A ANALISIS KINERJA PEGAWAI MENGGUNAKAN ALGORITMA K-MEANS PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BENGKULU TENGAH - Oktara, Panggi; Yulianti, Liza; Fredricka, Jhoanne (Jurnal Media Infotama, 2021)
The Central Bengkulu Regency Education and Culture Service is a government agency in Central Bengkulu Regency, Bengkulu Province. Performance assessment using a predetermined form. Every year an employee performance evaluation will be carried out to make decisions and consideration in determining the performance obtained by the employee. The criteria for evaluating employee performance at the Central Bengkulu Regency Education and Culture Service are Service Orientation, Integrity, Commitment, Discipline, Cooperation and Leadership. The employee performance application at the Central Bengkulu Regency Education and Culture Service was created using the Visual Basic .Net programming language and SQL Server 2008 Database. The grouping of employee data is based on the results of performance assessments that have been carried out, namely assessment orientation, integrity, commitment, discipline, cooperation and leadership. The results of grouping employee performance assessment data showed that the number of employees in the high cluster (Cluster I) was 22% and the number of employees in the low cluster (Cluster II) was 82%. The functionality of the application is running well and the application can help the Central Bengkulu Regency Education and Culture Office in knowing the performance of its employees based on 2 groups, namely the high cluster and the low cluster.